REKRUTMEN KARYAWAN RUMAH SAKIT NUR HIDAYAH BANTUL YOGYAKARTA DALAM PRESPEKTIF MANAJEMEN ISLAM - Hidayatullah, Hidayatullah; Hapsari, Cinthia Mutiara; Kuswanto, Kuswanto; Marlina, Marlina (LPPM Akademi Manajemen Administrasi Yogyakarta, 2021)
One of the efforts that must be made to achieve the goals of the organization or company is to have human resources who have the ability and expertise in each field. HR or often termed as labor or employees in the company, is the driving force of all activities carried out so that the company or organization runs smoothly and effectively. Nur Hidayah Hospital, Bantul Yogyakarta, in meeting the need for human resources, recruits employees through several stages. This study describes the stages in employee recruitment at Nur Hidayah Hospital. In addition, it also describes the views of Islamic management on employee recruitment at Nur Hidayah Hospital. The methodology of this research is descriptive qualitative using data collection methods through observation, documentation, and interviews. From this study it was concluded that the recruitment of employees at the hospital. Nur Hidayah is carried out directly or indirectly. While the view of Islamic management on employee recruitment at Nur Hidayah Hospital is that employee recruitment is actually the initial task that must be carried out by a leader in finding and selecting prospective employees to occupy predetermined job posts